2017
DOI: 10.3390/molecules22122144
|View full text |Cite
|
Sign up to set email alerts
|

Pyrene-Based Blue AIEgen: Enhanced Hole Mobility and Good EL Performance in Solution-Processed OLEDs

Abstract: Organic luminogens with strong solid-state emission have attracted much attention for their widely practical applications. However, the traditional organic luminogens with planar conformations often suffer from the notorious aggregation-caused quenching (ACQ) effect in solid state for the π–π stacking. Here, a highly efficient blue emitter TPE-4Py with an aggregation-induced emission (AIE) effect is achieved by combining twisted tetraphenylethene (TPE) core and planar pyrene peripheries. When the emitter was s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 25 publications
0
11
0
1
Order By: Relevance
“…48 Furthermore, Yanget et al reported the highly efficient blue emitter TPE-4Py 26 with an AIE effect, which is achieved by a combination of a twisted tetraphenylethene (TPE) core and planar pyrenes on the periphery. 49 Its EL efficiency was enhanced in doped OLEDs, at high doping concentration (50%), with a current efficiency up to 4.9 cd A À1 at 484 nm (Fig. 17).…”
Section: Tpe-like Pyrene-based Aiegensmentioning
confidence: 93%
“…48 Furthermore, Yanget et al reported the highly efficient blue emitter TPE-4Py 26 with an AIE effect, which is achieved by a combination of a twisted tetraphenylethene (TPE) core and planar pyrenes on the periphery. 49 Its EL efficiency was enhanced in doped OLEDs, at high doping concentration (50%), with a current efficiency up to 4.9 cd A À1 at 484 nm (Fig. 17).…”
Section: Tpe-like Pyrene-based Aiegensmentioning
confidence: 93%
“…Because the n-butyl group in BCz-nBuPh exhibited less steric hindrance than the t-butyl group in BCz-tBuPh , molecules of BCz-nBuPh within the film exhibited a strong degree of molecular aggregation. t-Butyl groups have been introduced to blue emitting molecules to prevent molecular quenching [ 21 , 22 ]. BCz-tBuPh with t-butyl groups was expected to yield better host materials than BCz-nBuPh with regard to thermal and optical properties.…”
Section: Resultsmentioning
confidence: 99%
“…Pyrenes have also been employed to decorate TPE instead of being located at the core of the structure [ 67 ]. In this case, the Suzuki coupling between a boronic acid derivative of 2,7-ditertbutylpyrene and 1,1,2,2-tetrakis(4-bromophenyl)ethene furnished oligomer 23 .…”
Section: Fully Conjugated Oligomersmentioning
confidence: 99%